Reorientation of Law Enforcement Based on Pancasila - Vincentius Patria Setyawan (SYARIAH : Jurnal Ilmu Hukum, 2023)
Pancasila is the basis of the state as well as the source of all sources of law. Indonesia as a state of law, all aspects of the life of the country must be regulated by law, and this includes aspects of law enforcement. The fact that there is law enforcement in Indonesia makes it a consideration to reorient law enforcement in Indonesia, by returning it to Pancasila values. This article was written using a normative legal research method with a conceptual and statutory approach. The results of this study are that law enforcement in accordance with Pancasila is social justice law enforcement, which means a balance between the interests of the community.